The Importance of Service Quality in Building Customer Satisfaction and Loyalty in the Service Industry: A Case Study of Hunky Dory Barbershop - Muhammad Fakhrul Arifin; Hartoyo Hartoyo; Eva Z Yusuf (Bina Nusantara University, 2020)
The research aimed to see how the influence of service quality was on customer satisfaction and loyalty in Hunky Dory Barbershop. The research was an explanatory research. The sampling technique was done by giving questionnaires to random customers who came to Hunky Dory barbershop. Analysis applied Structural Equation Modeling-Partial Least Square (SEM-PLS) to see the relationship between variables of service quality, price perception, trust, customer satisfaction, and loyalty. The results show that all variables affect customer satisfaction and loyalty, except price perception. It does not affect satisfaction since customers do not consider price when they are satisfied with the service. There is a significant positive relationship between service quality and loyalty which shows that the higher the service quality is, the higher the loyalty will be.